Evaluasi Program Pemberian Makanan Tambahan Menggunakan Satu Hari Satu Telur Pada Balita Stunting di Puskesmas Multiwahana Kota Palembang - Rahayu, Rizka Sri; Ainy, Asmaripa; Budi, Iwan Stia; Lubis, Adelina Irmayani (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2025)
In Indonesia, stunting has emerged as a critical national issue that must be addressed as it significantly affects the potential and quality of human resources. One of the initiatives implemented by Puskesmas Multiwahana to combat stunting is the evaluation of the supplementary feeding program, specifically the 'One Egg per Day' initiative for stunted toddlers. This study aimed to assess the effectiveness of the program using a qualitative approach, employing in-depth interviews with nine informants. The evaluation framework consists of three components: Input (Man, Money, Material, Method), Process (Planning, Organizing, Actuating, Controlling), and Output (Program Coverage). Findings indicated that the 'One Egg per Day' program at Puskesmas Multiwahana has been effectively implemented, successfully providing eggs to stunted toddlers. However, several challenges remain, particularly in monitoring consumption and distribution. In conclusion, the program faces limitations in supervision frequency and relies primarily on weight and height measurements for evaluation, highlighting the need for improved monitoring mechanisms to enhance its overall impact.